Revisiting enduring values - Gorman, Michael (JLIS.it, 2015)
The paper discusses the nature of values in general and the nature and utility of the values of librarianship.  Delineates the changes that have occurred and are occurring in the wider world and the nature of change; also the importance of values in providing a framework for dealing with present and future change.  Stresses the centrality of the human record to societal progress, the place of the human record in cultural heritage, and the central purpose of libraries in facilitating interaction with the human record and furthering the transmission of cultural heritage.  Urges a turning away from the alien value systems of information technology, consumerism, materialism, and corporate management, and a consequent set of alliances between libraries and a wide range of cultural institutions and associations.